Analisis Wacana Kritis pada Pemberitaan Grup Band Sabyan Gambus - Faisal Fahri; Syairal Fahmy Dalimunthe; M. Surip (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
In general, this paper discusses and describes critical discourse analysis on the news of "Sabyan Gambus Band Group" using Norman Fairclough's theory. Through this analysis of Norman Fairclough's critical discourse, it is possible to find findings about the ideology contained in the news in various existing media. The method used in this research is descriptive qualitative method, listening method, and literature study. The stages of this research are divided into three categories, namely the data collection stage, the data classification stage, and the data analysis stage. Data analysis techniques used include data reduction, data presentation, and drawing conclusions. The results of data analysis are presented in a narrative and descriptive manner. The theory used in this study is a three-dimensional model from Norman Faircglough, namely the micro, mesostructural, and macrostructural dimensions. The results of this study indicate that the five news media, which is abbreviated as S3PD, explain various kinds of realities that appear with different characters in the selection of titles and discourses. Based on Microstructural Analysis, there are linguistic studies; based on Mesostructural Analysis, there is the use of five discourse media and text consumption; and based on Macrostructural Analysis in the coverage of the Sabyan Gambus Band Group, it was found that the current social level circulating in society. Four out of five media covering the Sabyan Gambus Band Group focused on the negative aspects, while only one focused on the positive.